Cobalt‐Based Electrocatalysts as Air Cathodes in Rechargeable Zn–Air Batteries: Advances and Challenges. Issue 12 (23rd October 2021) - Yang, Fan; Gao, Xingyuan; Xie, Jinhao; Liu, Xiaoqing; Jiang, Jiuxing; Lu, Xihong
Abstract : Rechargeable Zn–air batteries (ZABs) are efficient devices for renewable energy conversion and storage. One of the bottlenecks of current ZAB technology lies in the lack of robust and cost‐effective catalysts for effectively driving oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) reactions simultaneously at air electrodes. Owing to the high intrinsic catalytic activity, low cost, and abundant reserves, cobalt (Co)‐based nanomaterials have become one of the most promising bifunctional oxygen electrocatalysts. Recently, considerable efforts have been devoted to developing high‐performance ZABs by using Co‐based compounds as cathodes. Herein, the recent progress of Co‐based electrocatalysts in ZABs is covered in four categories, including cobalt chalcogenides, cobalt oxides, Co‐based layered double hydroxides (LDHs), and Co–N–C structures. In each category, synthesis approaches and modification strategies are illustrated, and the structure–performance relationships are discussed. To conclude, a brief summary of current achievements and challenges is provided, and a prospect for future explorations is proposed. Abstract : This review introduces the recent advance of cobalt‐based air cathode for high‐performance Zn–air batteries. The first part elucidates the underlying mechanisms of electrocatalytic reactions on the air electrodes. In the second part, the synthesis approaches and modification strategies are summarized, and the structure–performance relationships are discussed. In the end, the key challenges and future opportunities of this direction are concluded.